LEGAL ASPECTS OF DIRECT APPOINTMENT OF PROCUREMENT OF MATERIALS FOR THE ELECTION CAMPAIGN OF THE REGENCY OF THE REGENT AND THE DEPUTY REGENT IN MALINAU IN 2015 - Esti Royani; Rini Iriani (Awang Long Law Review, 2022)
The purpose of this study is to find out and analyze the arrangements regarding the procurement of campaign materials, when tenders generally fail to be carried out and to analyze direct appointments in the procurement of campaign materials for the election of the Regent and Deputy Regent in Malinau in 2015 has met the general principles of good governance. Elections for Regional Heads and Deputy Regional Heads which are currently being held through simultaneous regional elections in 2015 have changed the face of implementing democracy at the regional level. By directly electing regional leaders, the people are given the opportunity to determine who is the policy maker in their region, at the same time every citizen is given the right to run as a policy maker. In this study, the researcher used a juridical-normative approach by analyzing legal principles in which the researcher tried to focus on legal studies and their prevailing principles in society and then described the existing phenomena and analyzed them systematically. The results of this research show that the Malinau KPU has conducted two bidding but failed, so direct appointment was made, this action has met the principles and norms of the prevailing law.